PELATIHAN PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM MENYUSUN BAHAN PEMBELAJARAN BAGI GURU PAUD DI KABUPATEN JAYAPURA - Sirjon, Sirjon; Reba, Yansen Alberth; Hilapok, Falentina (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The educational challenges in Sentani, Jayapura Regency, cannot be overlooked. PAUD (Early Childhood Education) teachers in Sentani face several obstacles that impact the quality of learning, including limited human resources, insufficient training, and restricted use of technology. This activity aims to provide training to PAUD teachers in Sentani, Jayapura Regency, to enable them to utilize Artificial Intelligence (AI) technology in preparing adaptive learning materials tailored to the needs of early childhood education. The training was conducted at Kindergarten Kemala Bhayangkari 04 Sentani, Jayapura, from June 6 to June 8, 2024. The target group consisted of PAUD teachers in Jayapura Regency, with a total of 31 participants in attendance. The methods employed in this service activity included training sessions and workshops. The training covered fundamental AI concepts, AI applications in education, and practical implementation in the context of early childhood education. The evaluation methods used were observations and participant feedback. The results of the activity indicate that: 1) Participants were active and successfully completed the training sessions with excellent outcomes, 2) Participants' understanding of the basic concepts of AI and its application in education significantly improved, 3) There was a notable increase in participants' ability to implement AI technology, 4) The quality of the learning materials produced was rated 100% at a minimum standard of "good," 5) The training was deemed effective by the participants, 6) Participants' confidence in using AI in their teaching practices increased. --- Tantangan pendidikan di Sentani, Jayapura tidak dapat diabaikan. Guru PAUD di Sentani dihadapkan pada beberapa tantangan yang mempengaruhi kualitas pembelajaran, seperti keterbatasan sumber daya manusia, kurangnya pelatihan, dan keterbatasan penggunaaan teknologi. Kegiatan ini bertujuan untuk memberikan pelatihan kepada guru PAUD yang ada di Sentani Kabupaten Jayapura sehingga dapat memanfaatkan teknologi Artificial intelligence (AI) dalam menyusun bahan pembelajaran yang adaptif dan sesuai dengan kebutuhan anak usia dini. Kegiatan pelatihan ini dilaksanakan di TK Kemala Bhayangkari 04 Sentani Jayapura pada tanggal 6-8 Juni 2024. Kayalak sasaran adalah guru PAUD di Kabupaten Jayapura dengan jumlah yang hadir sebanyak 31 orang. Metode yang digunakan dalam kegiatan pengabdian ini adalah metode pelatihan dan workshop. Pelatihan mencakup konsep dasar AI, aplikasi dalam pembelajaran, dan praktik penggunaannya dalam konteks pendidikan anak usia dini. Metode evaluasi yang dilakukan adalah observasi dan tanggapan peserta. Hasil kegiatan pengabdian menunjukkan bahwa: 1) Peserta aktif dan berhasil menyelesaikan sesi pelatihan dengan sangat baik, 2) Tingkat pemahaman peserta tentang konsep dasar AI dan aplikasi AI dalam pendidikan meningkat, 3) Terjadi peningkatan kemampuan peserta dalam mengimplementasikan teknologi AI, 4) Kualitas bahan/perangkat pembelajaran yang dihasilkan 100% berada pada penilaian minimal cukup baik, 5) Pelaksanaan pelatihan dinyatakan efektif oleh peserta, dan 6) kepercayaan diri peserta meningkat untuk menggunakan AI dalam pembelajarannya.